Multi-segments conformal plan optimization for head and neck cancer - Doaa Ali Salih Khudair; Haydar Hamza Obaid Alabedi; Nabaa Mohammad Ali Ahmed Alazawy (Journal of the Pakistan Medical Association, 2024)
Objective: To evaluate better dose distribution with three-dimensional radiation therapy, and to compare it with multi-segmented treatment planning techniques in patients with head and neck cancer. Method: The prospective study was conducted at the Baghdad Centre for Radiation Therapy and Nuclear Medicine, Baghdad, Iraq, and comprised data of 50 patients with head and neck cancerous tumours from June 2021 to February 2022. There were 35 (70%) females and 15(30%) males. The mean age was 47.31 ± 3.95 years (range 19 – 69 years The patients had undergone computed tomography simulation. The images were exported to Monaco 5.1 for contouring by the radiation oncologist. The data was then imported to XiO planning system. Each plan was repeated twice; once with three-dimensional conformal radiation therapy and the other with field-in-field technique. Data was analysed using SPSS 24. Results: There were 50 patients whose data was analysed. The results showed significant differences between three-dimensional conformal radiation therapy and field-in-field techniques for dose coverage at 90% and 95% volumes (p<0.05). There was a significant difference between the two techniques for 2Gy dose (p<0.05), but the difference was not significant for 5Gy dose (p>0.05). Conclusion: The field-in-field treatment planning technique was found to be more effective than the three-dimensional conformal radiation therapy technique. Key Words: Nuclear, Radiation, Head and Neck Neoplasms, Tomography, Radiotherapy, X-rays